PERSEPSI PEMUDA TERHADAP PROFESI PETANI PADI DI KOTA SEMARANG - Mita Erliaristi; Kadhung Prayoga; Joko Mariyono (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The majority of youth today do not choose jobs as farmers because they are considered unprofitable for life. This study aims to: (1) analyze youth perceptions of the rice farming profession, (2) analyze the simultaneous or partial influence of income, capital, social environment, age and education factors on youth perceptions of the rice farming profession in Semarang City. implemented in the city of Semarang. The method of determining the sample using the cluster sampling method with a total sample of 125 people. The type of data used is primary and secondary data obtained by interview, observation, and documentation. The data analysis method used is descriptive analysis and multiple regression test. The results showed that this positive perception can be seen from the youth's perception of rice farmers with a positive view or in accordance with the youth's expectations of the rice farmers which can be seen in terms of income, capital, social environment, age and education. Pemuda agrees that rice farmers' income is adjusted to the area of land owned by farmers and farmers' income is fluctuating. The youth considered that to become a farmer it was not necessary to have private land because farmers could work on other people's land. Lack of capital can affect the income of rice farmers. Peers who are in the environment around the youth do not take lightly the rice farmer profession and the youth's parents do not support their children to become rice farmers. Youth considers that to become a rice farmer there is no certain age limit and youth is suitable to be a rice farmer. Youth during their education did not acquire knowledge about rice farmers. Youth considers that being a rice farmer requires knowledge, experience and skills..